Penolakan Sertifikasi Label Halal MUI Surabaya pada Produk “Mie Setan” Perspektif Hukum Islam dan Undang-Undang No 33 Tahun 2014 - Siti Nur Faiza (Maliyah : Jurnal Hukum Bisnis Islam, 2021)
This study discusses the rejection of the halal label certification on devil noodle products in the perspective of Islamic law and Law no. 33 of 2014. The results of the study concluded that the rejection of the halal label certification application based on SK46/Dir/LPPOM MUI/XII/14 and MUI Fatwa Number 4 of 2003 concerning Standardization of Halal Fatwas because the name of Satan is identic with the name of the enemy of Allah and it is feared that it can distance from remembering Allah and can be categorized as 'urf fasid (bad costome) that must be abandoned. Then, regarding the product name in Law no. 33 of 2014 is not an object that will be examined by halal auditors, but regarding the name and type of product, it is an initial file at the stage of submitting an application, then in article 33 of Law no. 33 of 2014 explains that the determination of product halalness is carried out by MUI in the MUI halal fatwa trial. In line with the conclusion above, the owner of the Surabaya devil noodle product must follow the procedure of LP POM MUI JATIM, namely changing the name of the devil with a good name, then for consumers who consume devil noodle, it is expected that the spicy level is adjusted to the body's ability and not excessive, and for LP POM MUI JATIM to be careful in accepting or rejecting the submission of MUI halal label certification, so that no party feels aggrieved or disappointed.